APLIKASI PENUNJUK ARAH LOKASI KAMPUS STIMATA MENGGUNAKAN TEKNOLOGI AUGMENTED REALITY - Satya Pratama, Andika; Anwar, Khoerul (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2013)
STMIK Pradnya Paramitha (STIMATA) is one of the private universities in the city of Malang. In mid-2008 , STIMATA campus occupies a new building that is on the road Admiral Adi Sucipto . Quite a lot of people who do not know exactly where the location of the new campus Stimata , especially those residing outside the city of Malang . One reason is the location of the campus is located quite far from the center of the city of Malang.Of these problems , solutions that can be applied is to develop an application on a mobile device that can be a signpost on Stimata campus locations . The application can be put on the official website Stimata so it can be downloaded by anyone who wants to know the location of the campus Stimata easily . Manufacturing applications such directions would be more attractive and easier to use if built using Augmented Reality technology.This study aims to build and develop applications on mobile devices by utilizing Augmented Reality technology that can be used as a pointing device for its direction . Applications will be implemented on a device built Android smartphone operating system . In operation this application uses GPS coordinates to two points , the coordinates of the location coordinates of the user and Stimata campus , while the implementation of Augmented Reality technology on the application will be used Mixare engine . This study starts from the design workflow applications , the main display interface design , core application development , to the creation of the menu interface provides useful features that are provided to the user.Â Â Key words : mobile applications, directions, smartphones, Android, Augmented Reality, MixareÂ